2021
DOI: 10.3389/fenrg.2021.751722
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Policy Analysis for Sustainable Aviation Fuel Production Technologies

Abstract: This paper quantifies the impact of different policy options on the economic viability of sustainable aviation fuel (SAF) production technologies. The pathways considered include isobutanol to jet from corn grain, hydroprocessed esters and fatty acids (HEFA) from inedible fats and oils, HEFA from palm fatty acid distillate, synthesized iso-paraffins from sugarcane, Fischer-Tropsch (FT) gasification and synthesis from municipal solid waste, and micro FT from wood residues. The policies considered include feedst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…These incentives for producing fuels with lesser GHG emissions may be combined with other subsidies, including those for certain feedstocks, output-based incentives and capital grants to further lower biofuel MFSPs. 48 Future studies that incorporate carbon policies and incentives would be complementary to the present technoeconomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These incentives for producing fuels with lesser GHG emissions may be combined with other subsidies, including those for certain feedstocks, output-based incentives and capital grants to further lower biofuel MFSPs. 48 Future studies that incorporate carbon policies and incentives would be complementary to the present technoeconomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is completed by considering the revenues of both the fuel sales and various government programs available for sustainable products. The impact of stacking the applicable incentives while balancing the process and feedstock costs required to qualify allows for the comparison of both fuel and environmental services revenues (Airlines for America, 2021; Wang et al, 2021). Policy support might be an effective method to incentivize SAF production in the United States, as demonstrated in renewable diesel production where the stacking of existing federal and state programs has been reported to generate enough income to cover production costs (Stratas Advisors, 2020).…”
Section: Sustainable Fuel Programsmentioning
confidence: 99%
“…While conventional jet fuel is valued exclusively on the energy content required to power the flight, SAF is required to meet these standards while also providing the environmental services to reduce the greenhouse gas emissions compared to conventional fuels (Martinez-Valencia et al, 2021). Government policies and corporate sustainability programs will be vital to aid the technological innovations needed to close the price gap between conventional and sustainable fuels (Moriarty et al, 2021;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it was later reported that the HEFA pathway, as with any other pathway, would not be profitable in the absence of government incentives [216]. The project medium Net Present Value (NPV) for all pathways is below zero, thereby suggesting government policy support for financial viability [217]. Furthermore, production cost estimates are higher for non-HEFA jet biofuels due to higher expenses for To the best of the authors' efforts, up to date, it was not possible to find in the literature any peer-reviewed work on the production of jet biofuels via enzymatic HEFA (or similar) pathway; as stated above, it is possible to find reports on the production of hydrocarbons from esters and fatty acids via enzymatic biocatalysis, but none of them goes further on the characterization of the product as a jet biofuel.…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…In fact, it was later reported that the HEFA pathway, as with any other pathway, would not be profitable in the absence of government incentives [216]. The project medium Net Present Value (NPV) for all pathways is below zero, thereby suggesting government policy support for financial viability [217]. Furthermore, production cost estimates are higher for non-HEFA jet biofuels due to higher expenses for feedstock and capital expenditure components [218].…”
Section: Techno-economic Analysismentioning
confidence: 99%